The Relationship Between Childhood Trauma and Borderline Personality Disorder: The Mediator Effect of Insecure Attachment - Wang, Yilin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Childhood trauma is a major cause of borderline personality disorder. Research shows that most patients diagnosed with borderline personality disorder report unhappy or shadowy childhood experiences in psychological assessments. Attachment may be one of the important mechanisms by which childhood trauma affects borderline personality disorder. Attachment styles have a strong influence on people. People with insecure attachment styles often show distrust of others and extreme language and behaviour. This is also a core symptom of borderline personality disorder. The aim of this study was to investigate whether insecure adult attachment styles mediate borderline personality disorder as a result of childhood trauma. In addition, a secure attachment style may have a positive effect on alleviating or even treating Borderline Personality Disorder. This study will investigate this aspect. It is hoped that this research will advance researchers' understanding of the impact of childhood trauma on Borderline Personality Disorder and its mechanisms, and provide theoretical and empirical support for interventions aimed at reducing Borderline Personality Disorder caused by childhood trauma.